A Comparison of the Relationship between Obesity and Earnings in the U.S. and Germany - John H. Cawley; Markus M. Grabka; Dean R. Lillard (Schmollers Jahrbuch, 2005)
This paper investigates and compares the relationship between obesity and earnings in the U.S. and Germany. Using data from the Panel Study of Income Dynamics (U.S.) and the German Socio-Economic Panel, instrumental variables models are estimated that account for the endogeneity of body weight. We find that, in both countries, heavier women tend to earn less. For example, obesity is associated with almost 20 percent lower earnings for U.S. and German women. We test for causality using IV models; these models suggest that weight may lower labor earnings for U.S. women. However, our IV results yield no evidence of a causal impact of weight on earnings for women in Germany or for men in either country.
Keywords: J71; J31; J10; I10; 330; Obesity; Weight; Labor Market Outcomes; IV estimation; Einkommen; Gesundheit; Vergleich; Deutschland; USA